FY2005 Supplemental Appropriations for Iraq and Afghanistan, Tsunami Relief, and Other Activities. (U.S. Congressional Research., 2005)
Provides overview of and context for Administration requests for FY2005 supplemental appropriations for DOD, foreign policy, and other activities, including for DOD operations in Iraq and Afghanistan, counterterrorism programs, and Indian Ocean tsunami relief. Examines cross-functional budget issues and specific policy issues involved in the supplemental appropriations request, and describes Congressional actions related to the appropriations request. Includes tables.